Dépistage de l’artériopathie oblitérante des membres inférieurs par la mesure de l'indice de pression systolique à la cheville au repos chez les patients hospitalisés pour syndrome coronarien aigu au service de cardiologie de l’établissement public hospitalier de Laghouat durant la période de 06 octobre 2021 au 19 janvier 2022 - Terkmani Chahrazed; Benkouider Fatima Elzahra (Université Amar Télidji Laghouat, 2022)
Introduction The PAD is a marker of systemic atherosclerosis, is associated with cardiovascular risk and cardiovascular death. This is a common disease but it is underestimated because it often remains asymptomatic for a long time.The detection of peripheral arterial disease is obtained by calculating the ankle brachial index(.ABI) .ABI is a simple, accessible and inexpensive way to assess the severity of atheromatous disease of the two lower limbs. Material and method This is a prospective observational study, carried out over a period of 3 months from October 6, 2021 to January 19, 2022 in the cardiology department of the public hospital establishment (EPH) of Laghouat. The aim of this work is to evaluate the prevalence of PAD detected by resting IPS in these patients. Results This prospective observational study, which collected 50 patients hospitalized for acute coronary syndrome, of whom 54% had SCAST+ and 46%SCAST-, a prevalence of PAD of 12% (n=06) was found. Among the 03 women and 03 men, i.e. sex ration of 1. .the most affected age group is between 55 and 75 years old with an average of 71.33 years. 33.33% (n=02) of active smoking patients, with a male predominance, 33.33% (n=02) are type 2 diabetics, 66.66% (n=04= are hypertensive and 83.33% are obese or overweight , 100% are sedentary and 100% of women are postmenopausal.The mean CT in patients with PAD was found to be 1.68g/l. personal cerebrovascular ATCDS (CVA/AIT) was found in 03 cases or 50% of our patients. The left ventricular ejection fraction is altered in 100% (n=06) of cases. 04 cases or 66.67% of our patients have stress ischemia while 02 patients or 33.33% of cases have permanent ischemia without permanent trophic disorders, while 90% of our patients were asymptomatic. Conclusion Despite the existence of certain limitations, such as the non-representativeness of the sample, the small number of this study revealed a prevalence of PAD at 12%, it falls within the range of prevalence's (6.9 to 19.1 %) reported in the literature
CD-ROM